Gut-associated metabolites and diabetes pathology: a systematic review - Gough, Katelyn L.; Dando, Samantha J.; Teasdale, Stephanie L.; Feigl, Beatrix; Huygens, Flavia; Pelzer, Elise S. (Frontiers in Endocrinology, 2025)
BackgroundAs the global prevalence of diabetes mellitus reaches epidemic proportions, research into new therapeutic targets that address the underlying pathomechanisms of the disease is essential. Recent studies have elucidated the fundamental role of intestinal metabolic pathways in human health and disease processes and yet, the underlying cause of metabolic dysregulation in diabetes is largely unknown. Therefore, this systematic review aimed to identify the intestinal metabolomic profiles associated with gestational diabetes mellitus, type 1 diabetes mellitus, pre-diabetes mellitus, and type 2 diabetes mellitus.MethodsA systematic review of databases and grey literature repositories identified primary literature published between 2005 and 2022, that investigated patterns of human- and microbial-derived metabolite concentration in individuals with diabetes.ResultsData extracted from thirty-four eligible studies revealed 272 metabolites that were associated with diabetes diseases; the majority correlated with incidence of type 2 diabetes mellitus only. Inter-study discrepancies were reported based on the biospecimen type used in metabolomic analyses, namely blood, stool, or urine.ConclusionThe results of this review emphasise the paucity of research investigating gestational and type 1 diabetes mellitus intestinal metabolic perturbations. Furthermore, the potential for inter-study bias in downstream metabolomic analyses based on sample type warrants further investigation.